2006
DOI: 10.1002/cphc.200500401
|View full text |Cite
|
Sign up to set email alerts
|

Does Silica Surface Catalyse Peptide Bond Formation? New Insights from First‐Principles Calculations

Abstract: The role that silica surface could have played in prebiotic chemistry as a catalyst for peptide bond formation has been addressed at the B3LYP/6-31+G(d,p) level for a model reaction involving glycine and ammonia on a silica cluster mimicking an isolated terminal silanol group present at the silica surface. Hydrogen-bond complexation between glycine and the silanol is followed by the formation of the mixed surface anhydride Si(surf)-O-C(=O)-R, which has been suggested in the literature to activate the C=O bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 27 publications
5
87
2
Order By: Relevance
“…Furthermore, the role of silica has been already highlighted in previous studies on mineral-assisted condensation. In comparison, it was reported that the adsorption of Gly on silica reduced the E a by only 10% [40]. In our experiment, HAP decreased the E a of Gly condensation by more than 60%.…”
Section: Resultscontrasting
confidence: 61%
“…Furthermore, the role of silica has been already highlighted in previous studies on mineral-assisted condensation. In comparison, it was reported that the adsorption of Gly on silica reduced the E a by only 10% [40]. In our experiment, HAP decreased the E a of Gly condensation by more than 60%.…”
Section: Resultscontrasting
confidence: 61%
“…Drawn from data of Refs. 74,223 The value of 1699 cm -1 represents the maximum bathochromic shift (-85 cm -1 ) of the (C=O) fingerprint mode and results from the H-bonding with two different terminal silanol groups (see "double H-bonding" interaction pattern in Figure 62). Theoretical results indicate that the interaction of Gly with silica surfaces may also take place with only one SiOH group through the "single H-bonding" interaction pattern (see Figure 62).…”
Section: Gas-phase Interactionmentioning
confidence: 99%
“…Due to the relatively small size of such systems, ab initio and DFT calculations could be carried out for these computational studies. [15][16][17] Of particular interest to the present contribution is the work of Rimola et al [16] These authors claimed that a direct glycine-silica interaction is possible without the need of having water molecules as a solvent. Moreover, the hydroxylated silica surface was shown to stabilize the glycine zwitterionic form.…”
mentioning
confidence: 98%